Handgrip strength and weight predict long-term mortality in acute kidney injury patients. (February 2017) - Xavier, S.P.; Goes, C.R.; Bufarah, M.N.B.; Balbi, A.L.; Ponce, D.
Summary: Introduction: Surviving acute kidney (AKI) patients have a higher late mortality compared with those admitted without AKI. The negative impact of malnutrition on the early outcome of AKI patients has recently been confirmed by various studies. However, its impact after hospital discharge has not been studied. The objective of the study was to determine the role of anthropometric measurements and handgrip strength as predictors of mortality 180 days after discharge. Methodology: Eighty-two survivors AKI patients who were older than 18 y old and followed by AKI team were prospectively evaluated. Patient's characteristics were recorded, anthropometric measurements were taken, handgrip strength (HGS) was measured, subjective global assessment and bioimpedance were applied and blood samples were collected during hospitalization at first and last nephrologist evaluation and in after hospital discharge at 1 month, 3 and 6 months. Multivariable logistic regression was used to adjust confounding and selection bias. Results: Age was 62.3 ± 14.7 years, prevalence of hospitalization in medical wards of 71.6%, index of severity of AKI (ATN-ISS) was 28% and late mortality rates was 25.6%. Risk factors associated with late mortality were the number of comorbidities (HR = 1.79, 95% CI = 1.45–2.46, p = 0.04), cancer (HR = 1.89, 95 CI% = 1.48–3.16, p = 0.01), sepsis (HR = 1.47, 95% CI = 1.18–2.38, p = 0.03), no recovery of renal function at hospital discharge (HR = 1.46, 95% CI = 1.02–2.16, p = 0.03), malnutrition at first evaluation (HR = 1.58, 95% CI = 1.14–2.94, p = 001), the HGS value at the moment of last evaluation by nephrologist (HR = 1.81, 95% CI = 1.17–2.31, p = 0.04) and gain weigh < 1 kg between the moment at first evaluation by nephrologist and one month after hospital discharge (HR = 1.95, 95 CI% = 1.29–3.3, p = 0.02). Conclusion: HGS and gain weight were identified as predictors of late mortality. Simple and ease methods can be applied in AKI patients during and after hospitalization to diagnose nutritionally patients who are at higher risk for poor prognosis and, consequently intervention measures can be performed to improve survival in long-term.